Proposal of Two New Combinations, Twenty New Species, Four New Genera, One New Family, and One New Order for the Anamorphic Basidiomycetous Yeast Species in Ustilaginomycotina - Li, Yao-Yao; Wang, Man-Man; Groenewald, Marizeth; Li, Ai-Hua; Guo, Yun-Tong; Wu, Feng; Zhang, Bing-Qian; Tanaka, Eiji; Wang, Qi-Ming; Bai, Feng-Yan; Begerow, Dominik (Frontiers in Microbiology, 2022)
244 ustilaginomycetous yeast or yeast-like strains were isolated from soil, skin of animal or human, and plant material during the past 20 years. Among them, 202 strains represent 38 known species, whereas 42 strains represent 21 novel species based on the sequence analyses of the rDNA genes (18S rDNA, ITS regions, 26S rDNA D1/D2 domain) and three protein genes (RPB1, RPB2 and TEF1). In this study several novelties, one order, one family, four genera and 21 species are proposed.